Actual heating energy savings in thermally renovated Dutch dwellings - Majcen, Dasa (A+BE | Architecture and the Built Environment, 2016)
Since previous research has indicated large discrepancies between the theoretical and actual heating consumption in dwellings, it is important to know what savings renovations achieve in reality. The register of the Dutch social housing stock was analysed, containing dwelling thermal performance information of ca. 2 million dwellings between 2010 and 2013. Renovated dwellings were identified, providing insight into the performance gap before and after the renovation and the actual vs. the theoretical energy reduction of renovation measures. Improvements in efficiency of gas boilers (space heating and hot tap water) yield the highest energy reduction, followed by deep improvements of windows. Improving the ventilation yields a small reduction compared to other measures, however, it is still much larger than theoretically expected. High R and low U values of insulation are well predicted, as well as efficient heating systems whereas low R and high U values, local heating systems, changes from a non-condensing into a condensing boiler and upgrades from a natural ventilation system are not well predicted. The study therefore demonstrated that unrealistic theoretical efficiencies of heating systems and insulation values are causing a part of the performance gap.